(untitled) (Journal of Asian Development Studies, 2025)
The present study was designed to investigate the role of personality traits in the manifestation of deliberate self-harm. Understanding the psychological factors, such as specific personality traits, that underpin Deliberate Self-Harm (DSH) is crucial for developing effective screening, prevention, and intervention strategies, particularly in high-stress or specific population settings like military recruitment. A cross-sectional research design was used, and 56 male individuals, with a mean age of 19.86 (SD=2.42), were selected for the study. They were recruited from the Pakistan army at the Rawalpindi recruitment center over 2 months from March to April 2020. Data was collected by using the Minnesota Multiphasic Personality Inventory (MMPI), Urdu version and socio-demographic form. Results revealed that individuals with deliberate self-harm (N=28) with a mean age of 19.86 (SD=2.42) scored significantly high on hypochondriasis, depression, psychasthenia and social introversion of MMPI (p < .05) as compared to those without deliberate self-harm (N=28). Whereas scores on other clinical scales and validity scales of MMPI were non-significant (p > .05). It is concluded that certain personality traits are strongly linked with deliberate self-harm. There is a need for urgent measures in this direction, including the compilation of culturally specific scientific data at a national level. A multicenter study with homogeneous parameters on different issues of deliberate self-harm may be designed to achieve the nationwide data, which will help to understand the elements of intentional self-harm.